Sustainable Agriculture Systems in Vegetable Production Using Chitin and Chitosan as Plant Biostimulants - Shahrajabian, Mohamad Hesam; Chaski, Christina; Polyzos, Nikolaos; Tzortzakis, Nikos G.; Petropoulos, Spyridon A. (My University, 2021)
Chitin and chitosan are natural compounds that are biodegradable and nontoxic and have gained noticeable attention due to their effective contribution to increased yield and agro-environmental sustainability. Several effects have been reported for chitosan application in plants. Particularly, it can be used in plant defense systems against biological and environmental stress conditions and as a plant growth promoter-it can increase stomatal conductance and reduce transpiration or be applied as a coating material in seeds. Moreover, it can be effective in promoting chitinolytic microorganisms and prolonging storage life through post-harvest treatments, or benefit nutrient delivery to plants since it may prevent leaching and improve slow release of nutrients in fertilizers. Finally, it can remediate polluted soils through the removal of cationic and anionic heavy metals and the improvement of soil properties. On the other hand, chitin also has many beneficial effects such as plant growth promotion, improved plant nutrition and ability to modulate and improve plants' resistance to abiotic and biotic stressors. The present review presents a literature overview regarding the effects of chitin, chitosan and derivatives on horticultural crops, highlighting their important role in modern sustainable crop production; the main limitations as well as the future prospects of applications of this particular biostimulant category are also presented.
Keywords: Abiotic stress; Biotic stress; Chitosan derivatives; Oligochitosan; Vegetable crops